2016
DOI: 10.1007/s10551-016-3158-y
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the U.S. Public Accounting Profession’s Public Interest Discourse and Actions in Federal Policy Making

Abstract: Participation in the political process by the United States public accounting profession often blurs the role of the profession as advocates for the public interest with its role as advocates for its own private interests. In this study, we draw from prior theoretical and empirical work to investigate recent federal political activities of the public accounting profession to shed light on these sometimes contradictory roles. In particular, we investigate ten contemporary regulatory issues of interest to the AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…It appears that interest groups have captured the regulation in a way that prevented the Anti-slavery Commissioner from working independently to curb modern slavery. This evidence is consistent with how regulatory capture is defined within the diverse literature (Levine & Forrence, 1990;Hantke-Domas, 2003;Baudot et al, 2017;Dal Bó & Di Tella, 2003;Hines, 1991;Paisey & Paisey, 2012).…”
Section: Domination By Powerful Interestssupporting
confidence: 82%
See 2 more Smart Citations
“…It appears that interest groups have captured the regulation in a way that prevented the Anti-slavery Commissioner from working independently to curb modern slavery. This evidence is consistent with how regulatory capture is defined within the diverse literature (Levine & Forrence, 1990;Hantke-Domas, 2003;Baudot et al, 2017;Dal Bó & Di Tella, 2003;Hines, 1991;Paisey & Paisey, 2012).…”
Section: Domination By Powerful Interestssupporting
confidence: 82%
“…Anti-slavery activists believe that the Act has been influenced by corporations and some believe that there is little legal scope to hold organisations accountable for slavery practices. There is a view that the regulation has been captured by powerful corporate groups for their own interests (Baudot et al, 2017;Hantke-Domas, 2003;Hines, 1991;Levine & Forrence, 1990;Paisey & Paisey, 2012), and that modern slavery disclosures, therefore, attempt to reduce business risk and do not address and reduce the risks of those falling victim to modern slavery. The interviewees observed that risk minimisation agendas, among both regulators and corporations, may not automatically reduce the severity of modern slavery practices within global supply chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide additional insights, the analysis was re-administered (after adjusting for questions specific to the internal operations of audit firms) with 115 non-auditors [16]. This was necessary considering the potential for auditor bias against external regulation (Baudot et al, 2017;Daugherty et al, 2012;Lee, 1995). Including the views of senior executives, audit committee members and institutional investors also provides a more complete account of the implication of MAFR for audit practice.…”
Section: Differences Between Auditors and Non-auditorsmentioning
confidence: 99%
“…Accordingly, rather than becoming a struggle to classify or distinguish between different “levels” of power, authority, or influence (Lukes ; ), the issue of power almost turns into a mere political problem: how do people mobilize and manage available resources to achieve their ends and fulfill their purposes? For instance, the U.S. public accounting profession has been able to influence political processes by mobilizing significant resources such as time, money, and access to influential politicians (Baudot et al ).…”
Section: Theoretical Foundationsmentioning
confidence: 99%